Knorpelregenerative Eingriffe am Hüftgelenk: was ist machbar? - Landgraeber, Stefan; Jäger, Marcus; Fickert, Stefan (Der Orthopäde, 2017)
Localized cartilage defects at the hip are mainly caused by pre-arthritic deformities, particularly by cam-type femoroacetabular impingement (FAI). Timely elimination of symptomatic deformities can prevent further progression such as cartilage defects. As the defects mostly occur in the anterolateral part of the acetabulum, they can be easily treated either by open surgery or by arthroscopy. To date the most effective methods of treatment are bone marrow stimulation, with or without a covering of biomaterials, and autologous chondrocyte transplantation. In selected cases, readaptation of the damaged cartilage can be attempted by biological procedures. In the present article, the findings reported in current studies on these procedures are summarized and discussed in detail. An outlook is given regarding possible future treatment concepts.
Online publiziert: 27. Oktober 2017
Gesehen am 27.06.2018